Global evolution and dynamics of the geomagnetic field in the 15–70 kyr period based on selected paleomagnetic sediment records - Panovska, Sanja; Korte, Monika; Liu, Jiabo; Nowaczyk, Norbert (Journal of Geophysical Research: Solid Earth, 2021)
Reconstructions of the geomagnetic field on long timescales are important to understand the geodynamo processes in the Earth’s core. The geomagnetic field exhibits a range of variations that vary from normal, dipole–dominated secular variation to geomagnetic excursions and reversals. These transitional events are associated with significant directional deviations and very low intensities. Here we present a new, global geomagnetic field model spanning the period 70–15 ka (GGFSS70) that includes three excursions: Norwegian–Greenland Sea, Laschamps, and Mono Lake/Auckland. The model is built from nine globally distributed, high–resolution, well–dated, sedimentary paleomagnetic records. The GGFSS70 indicates that the axial–dipole component changed sign for about 300 years in the middle of the Laschamps excursion (41.25–40.93 ka). The energy comparison at the Earth’s surface reveals that the axial–dipole energy is always higher than the non-axial-dipole except over the Laschamps. In the other two excursions, the axial-dipole is reduced by about one order of magnitude for the Norwegian–Greenland Sea excursion and less for the Mono Lake/Auckland. At the core–mantle boundary, the large–scale non-axial-dipole power is comparable to the axial-dipole power, except over the excursions when the axial-dipole decreases, though less clearly for the Mono Lake/Auckland excursion. The axial dipole moment over the 15–70 ka varies from 0 to 8 ×1022 Am2, with an average and standard deviation of 5.1±1.5 ×1022Am2. The Laschamps excursion is associated with growth and poleward movement of reversed flux patches and reversed field in the tangent cylinder at the excursion midpoint, which is not the case for the other two excursions. Plain Language Summary Earth possesses a magnetic field that is constantly changing in time and space. Its source is located in the outer core and the mechanism by which the geomagnetic field is generated is known as the geodynamo. Studying the field on long timescales contributes to a better understanding of ...